Binding characterization of the targeting drug AIMPILA to AFP receptors in human tumor xenografts - Janneta Tcherkassova; Sergei Tsurkan; Galina Smirnova; Julia Borisova; Ricardo Moro; Helen Treshalina (Tumor Biology)
The main objective of this study was the characterization of preclinical tumor models based on their expression of alpha-fetoprotein receptor (RECAF) for targeting cancer cells with a new non-covalent complex (AIMPILA) containing alpha-fetoprotein as the carrier and Atractyloside as an apoptosis-inducing agent. For that purpose, we measured the amount of RECAF in the homogenates of the grafted tumors T47D and SW620 and in HepG2 cell extracts. We also determined the alpha-fetoprotein binding specificity of the targeting drug AIMPILA using a solid-phase chemiluminescent assay with AIMPILA-Acrdidinium. We found that RECAF is practically absent from healthy mice tissues (100 Units/mg) where in malignant cells, the amount of alpha-fetoprotein receptors follows this order: T47D (9152 Units/mg) > HepG2 (4865 Units/mg) > SW620 (2839 Units/mg). This agrees with our findings regarding AIMPILA-induced tumor growth inhibition (T47D (T/C = 22%) > HepG2 (T/C = 51%) > SW620 (T/C = 70%), where T/C is the ratio of tumor volume in treated vs control animals). Our results demonstrate that the therapeutic response to the targeting drug AIMPILA strongly depends on the RECAF expression by human tumors and confirms the choice of the tumor models used for an AIMPILA preclinical study.